Relationship of Antiviral Proteins with Retroelements in the Brain in Pathogenesis of Neurodegenerative Diseases - Mustafin, Rustam Nailevich (Current Proteomics, 2024)
FUS (fused in sarcoma protein), beta-amyloid, tau, alpha-synuclein, and TDP-43, which are involved in neurodegenerative diseases (NDDs) pathogenesis, are characterized by antiviral properties. These proteins are inhibitors of retroelements, being activated in response to retroelement expression products. This is due to the evolutionary relationship between retroelements and exogenous viruses. During aging, proteinopathy of the listed antiviral proteins with their predisposition to aggregation and dysfunction, as well as pathological activation of retroelements, is observed in the normal brain. However, these processes are significantly aggravated in NDDs due to the influence of the many polymorphisms associated with them, located in the intergenic and intronic regions where the retroelement genes are localized. These polymorphisms may be associated with NDDs due to pathological activation of specific retroelements and the ability of their expression products to abnormally interact with antiviral proteins. As a result, a “vicious circle” is formed in which transcripts and proteins of retroelements stimulate the expression of antiviral proteins, which form abnormal aggregates that are unable to inhibit retroelements. This, in turn, causes the activation of retroelements and the progression of the pathology. The initiating factors of the described mechanisms may be viral infections. Epigenetic processes in NDDs are accompanied by changes in the expression of specific microRNAs, some of which evolved from retroelements. An analysis of scientific literature has revealed 41 retroelement-derived microRNAs characterized by low expression in NDDs. To confirm the above theory, information was searched in the Scopus, WoS, and NCBI databases.
Keywords: viruses